2020
DOI: 10.3389/fchem.2020.00184
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Graphene Oxide Thin Films for Anti-tumor Drug Delivery to Melanoma Cells

Abstract: Since Graphene discovery, their associated derivate nanomaterials, Graphene Oxide (GO) and reduced-GO were in the forefront of continuous developments in bio-nano-technology due to unique physical-chemical properties. Although GO nano-colloids (GON) were proposed as drug release matrix for targeting cancer cells, there is still a concern regarding its cytotoxicity issues. In this study, we report on the fabrication of functional GON bio-coatings by Matrix-Assisted Pulsed Laser Evaporation (MAPLE) to be used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Clinical studies have demonstrated that HDACi can affect different biological processes ( 21 ). In the present study, we explored the direct effects of TSA on endothelial cell gene expression, proliferation, and tube formation.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated that HDACi can affect different biological processes ( 21 ). In the present study, we explored the direct effects of TSA on endothelial cell gene expression, proliferation, and tube formation.…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic, organic, hybrid coatings: Chitosan/ bio-mimetic apatite [61], CaPs, biopolymers [62,63] Levan and Chitosan blends [64], Graphene Oxide, BSA protein, drugs [65]/Implant devices, drug delivery, model surfaces.…”
Section: Combinatorial-matrix Assisted Pulsed Laser Evaporation (C-ma...mentioning
confidence: 99%
“…Since then, MAPLE has evolved to produce a broad spectrum of organic, inorganic, and hybrid coatings [109][110][111][112] for various biomedical applications as well as for energy [113][114][115], sensing [116][117][118], wearable electronics, and photonic devices [98,119]. Indeed, although initially designed for polymers, the method proved successful for a large variety of compounds such as proteins [106,107], enzymes [120,121], polysaccharides [103,122,123], calcium phosphates [24,55,124,125], nanoparticles [126,127], proteins and drug functionalized graphene oxide [65], or carbon nanostructures embedded in organic matrices [128]. Its maturity has already been achieved and existing commercial installations fulfil the anticipations of the scientific community [129].…”
Section: Matrix Assisted Pulsed Laser Evaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…The graphene family materials, including graphene oxide (GO), reduced/functionalized graphene oxide (rGO), graphene quantum dots, graphene nanoribbons, 3D (three-dimensional) graphene foam, and graphene nanopores, all are known to exert enormous effects in various biomedical applications. These materials were tried as antibacterial [25,26], anticancer [27,28], drug delivery [29][30][31], bio-sensing [32][33][34], and bio-imaging [35,36] processes owing to their differential interactions with biosystems and biomolecules under in vivo and in vitro conditions. This potential ascended from the characteristic physical, chemical, and mechanical properties of NPs and flakes to participate in biological processes at subcellular, cellular, and upcellular levels and scales.…”
Section: Introductionmentioning
confidence: 99%